PARTISIPASI TOKOH MASYARAKAT DALAM TOLERANSI UMAT BERAGAMA - Muzaki, Muzaki (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
The necessity of efforts to build harmony among religious believers in Indonesia recently increased significantly.This can be seen from the proliferation activities of interreligious dialogue in the regions. Strategic step for the future is to buildmutual understanding, cooperation, and appreciates other religion. To build a harmonious religious tolerance was necessaryactive role of all elements of the nation regardless of individual differences in beliefs, not to mention his own involvement in theorganization that allows for participation, such as with an active role through the Political Parties (Party), Non-GovernmentalOrganization (NGO) or other mass organizations (CBOs) and other social activities